Comparison of new combined event performance by performance level in modern pentathlon athletes - Kim, Y.-S.; Yoon, J.-R.; Hur, S. (Exercise Science, 2016)
PURPOSE: The purpose of this study was to provide basic data for a training program that could improve athletic performance by comparing the new combined event results through the GPS analysis with 9 high level (n=9) and low level (n=7) divided by performance level in male modern pentathlon athletes. METHODS: Subjects were wearing the ultra portable GPS receiving device in the back and chest. RESULTS: The result of this study was showed that the overall new combined event performance, total running, total shooting and transition time had statistically significant differences, and that the high level athletes were more rapid than the low level athletes. Each phases running time and running velocity showed that it was the fastest in the 1 phase and was the slowest in the 3 phase. CONCLUSIONS: In conclusion, the records of the high level athletes those had relatively short shooting time was more decreased than that of the high level athletes in the overall combined event performance recode. Therefore, the training program which combine highly trained shooting technology and strong concentration training should be made for low level athletes.